The Mercantilist Index of Trade Policy. - Anderson, J; Neary, J (Centre for Economic Performance, LSE, 1998)
This paper develops and characterises an index of trade policy restrictiveness defined as the uniform tariff equivalent which maintains the same volume of trade as a given set of tariffs, quotas, and domestic taxes and subsidies. We relate this volume-equivalent index to the Trade Restrictiveness Index, a welfare-equivalent measure, and relate changes in both indexes to changes in the generalised mean and variance of the tariff schedule. Applications to international cross-section and time-series comparisons of trade policy show that the new index frequently gives a very different picture than do standard indexes.